Peningkatan Hasil Belajar Matematika Penjumlahan Bilangan Bulat Melalui Media Konkret Berbasis Multisensori pada Siswa Berkesulitan Belajar: Improving Mathematics Learning Outcomes in Integer Addition for Students with Learning Difficulties Using Multisensory-Based Concrete Media - Evitawanti Evitawanti; Bayu Pamungkas (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to improve seventh-grade students' mathematics learning outcomes in integer addition at SMPIT Daarussalaam through the implementation of multisensory-based instruction using concrete media. The study was motivated by the low learning outcomes of students with learning difficulties when performing integer addition operations. A Classroom Action Research (CAR) method was employed, conducted over two cycles; each cycle comprised the stages of planning, action implementation, observation, and reflection. The study took place in April 2026 at SMPIT Daarussalaam. The subjects were 27 seventh-grade students, consisting of 24 students without special needs and 3 students with learning difficulties. Data collection involved tests, observation, and documentation. The data were analysed using quantitative descriptive analysis to determine improvements in learning outcomes based on test scores and learning mastery. The results indicate that before the implementation of multisensory instruction using concrete media, students with learning difficulties had low understanding of integer addition concepts; this was evidenced by a pretest average score of 63.5, with most students struggling to grasp the concept of integers. Following the intervention—which utilised multisensory-based concrete media tailored to student characteristics, fostered active student engagement, and provided systematic guidance—student learning outcomes improved significantly, as demonstrated by an increase in the average posttest score to 88.07 compared to the initial baseline.